2024
DOI: 10.1177/02692163231222391
|View full text |Cite
|
Sign up to set email alerts
|

PALLiative care in ONcology (PALLiON): A cluster-randomised trial investigating the effect of palliative care on the use of anticancer treatment at the end of life

Marianne Jensen Hjermstad,
Aleksandra Pirnat,
Nina Aass
et al.

Abstract: Background: Effects on anticancer therapy following the integration of palliative care and oncology are rarely investigated. Thus, its potential effect is unknown. Aim: To investigate the effects of the complex intervention PALLiON versus usual care on end-of-life anticancer therapy. Design: Cluster-randomised controlled trial (RCT), registered at ClinicalTrials.gov (No. NCT01362816). The complex intervention consisted of a physician education program enhancing theoretical, clinical and communication skills, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…The authors of that study suggested that intervention adherence should be ensured before study start. Another Norwegian cluster-randomized trial investigating the effect of PC on the use of anticancer treatment at the EOL found no differences between the groups [ 42 ]. As in our study, the intervention did not have the desired effect, probably due to the HCPs having a too low fidelity to the intervention to change clinical practice [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of that study suggested that intervention adherence should be ensured before study start. Another Norwegian cluster-randomized trial investigating the effect of PC on the use of anticancer treatment at the EOL found no differences between the groups [ 42 ]. As in our study, the intervention did not have the desired effect, probably due to the HCPs having a too low fidelity to the intervention to change clinical practice [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another Norwegian cluster-randomized trial investigating the effect of PC on the use of anticancer treatment at the EOL found no differences between the groups [ 42 ]. As in our study, the intervention did not have the desired effect, probably due to the HCPs having a too low fidelity to the intervention to change clinical practice [ 42 ]. The reasons for insufficient implementation in our study are heterogenous and may include factors such as differences in hospital and primary care cultures, lack of management anchoring, different information and communications technology systems, and preconceptions about PC referrals [ 17 , 18 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%